Microleakage of Pit and Fissure Sealants after Using Different Occlusal Surface Preparation Techniques: An In Vitro Study - Hoobi, Nibal Mohammed (Journal of Baghdad College of Dentistry, 2016)
Background: The marginal seal is essential for sealant success because penetration of bacteria under the sealant might allow caries onset or progression. The aim of the present study was to estimate and compare the microleakage of pit and fissure sealant after various methods of occlusal surface preparation. Materials and methods: Thirty non-carious premolars extracted for orthodontic reasons were equally divided into three groups. In group one, occlusal fissures were opened with round carbide bur, in group two, occlusal surfaces of the teeth were cleaned with a dry pointed bristle brush and samples of group three were cleaned with a slurry of fine flour of pumice in water using rubber cup. Then fissures of all teeth were etched using 35% phosphoric acid gel prior to placement of Conseal F (SDI) light cured sealant, the teeth were thermocycled, then they were immersed in 1% methylene blue for 24hours. Each tooth was sectioned bucco-lingually to detect the microleakage. Results: Different levels of microleakage were observed among various groups, highest level was recorded for brushing group followed by pumice group, while round bur samples showed the least microleakage when compared with other groups. Statistically the difference was not significant between brushing and pumice groups, while it was significant between round bur and other groups Conclusion: Preparation of occlusal surface with round bur was very effective in reduction of microleakage in comparison with the traditional pumice slurry and bristle brush.